2001
DOI: 10.1103/physrevb.63.205205
|View full text |Cite
|
Sign up to set email alerts
|

Tight-binding molecular dynamics study of vacancy-interstitial annihilation in silicon

Abstract: We have studied the annihilation of a tetrahedral interstitial by a vacancy using molecular dynamics and a tight-binding model due to Goodwin-Skinner-Pettifor. At both 1473 and 1173 K, the annihilation process was dominated by the movement of the faster-diffusing vacancy. Once the vacancy moved to a nearest-neighbor position relative to the interstitial, annihilation was inevitable. As the initial distance between the T-interstitial and the vacancy increased, the number of pathways by which annihilation occurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…[8][9][10][11] Small vacancy defects have been of particular interest because they are a main source or a getter for mobile vacancies and interstitials, which are largely responsible for dopant transient enhanced diffusion and electrical deactivation in ultrashallow junction formation for Si-based electronic devices. [12][13][14][15][16][17] Previous theoretical studies [18][19][20][21] proposed "part of hexagonal ring" ͑PHR͒ and spherically shaped cluster ͑SPC͒ models for the structure of vacancy clusters. According to the models, the V 6 , V 10 , and V 14 PHR configurations are predicted to be particularly stable because of their relatively reduced number of Si-Si broken bonds.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10][11] Small vacancy defects have been of particular interest because they are a main source or a getter for mobile vacancies and interstitials, which are largely responsible for dopant transient enhanced diffusion and electrical deactivation in ultrashallow junction formation for Si-based electronic devices. [12][13][14][15][16][17] Previous theoretical studies [18][19][20][21] proposed "part of hexagonal ring" ͑PHR͒ and spherically shaped cluster ͑SPC͒ models for the structure of vacancy clusters. According to the models, the V 6 , V 10 , and V 14 PHR configurations are predicted to be particularly stable because of their relatively reduced number of Si-Si broken bonds.…”
Section: Introductionmentioning
confidence: 99%
“…7 possess energies that are higher than a completely dissociated cluster, even though they represent valid Stillinger clusters. These configurations correspond to the formation of additional defect structures such as Frenkel pairs ͑interstitial-vacancy pairs͒ 34 and other types of disordered states, and suggest a mechanism for amorphization and even crystal melting.…”
Section: A Absolute Probability Distributions and Density-of-states mentioning
confidence: 96%
“…Tight-binding molecular dynamics (MD) studies were performed for pair recombination in Si (19,20). It was found that the energy barrier for pair recombination varies between 0 and 1.1 eV depending on the V-I distance and also the site of I.…”
Section: Dft Molecular Dynamics Approach For the Recombination Of V A...mentioning
confidence: 99%